Apigenin and Rutaecarpine reduce the burden of cellular senescence in bone marrow stromal stem cells - Ali, Dalia; Okla, Meshail; Abuelreich, Sarah; Vishnubalaji, Radhakrishnan; Ditzel, Nicholas; Hamam, Rimi; Kowal, Justyna M.; Sayed, Ahmed; Aldahmash, Abdullah; Alajez, Nehad M.; Kassem, Moustapha (Frontiers in Endocrinology, 2024)
Osteoporosis is a systemic age-related disease characterized by reduced bone mass and microstructure deterioration, leading to increased risk of bone fragility fractures. Osteoporosis is a worldwide major health care problem and there is a need for preventive approaches. Apigenin and Rutaecarpine are plant-derived antioxidants identified through functional screen of a natural product library (143 compounds) as enhancers of osteoblastic differentiation of human bone marrow stromal stem cells (hBMSCs). Global gene expression profiling and Western blot analysis revealed activation of several intra-cellular signaling pathways including focal adhesion kinase (FAK) and TGFb. Pharmacological inhibition of FAK using PF-573228 (5 uM) and TGFb using SB505124 (1uM), diminished Apigenin- and Rutaecarpine-induced osteoblast differentiation. In vitro treatment with Apigenin and Rutaecarpine, of primary hBMSCs obtained from elderly female patients enhanced osteoblast differentiation compared with primary hBMSCs obtained from young female donors. Ex-vivo treatment with Apigenin and Rutaecarpine of organotypic embryonic chick-femur culture significantly increased bone volume and cortical thickness compared to control as estimated by uCT-scanning. Our data revealed that Apigenin and Rutaecarpine enhance osteoblastic differentiation, bone formation, and reduce the age-related effects of hBMSCs. Therefore, Apigenin and Rutaecarpine cellular treatment represent a potential strategy for maintaining hBMSCs health during aging and osteoporosis.